Acculturation of Islamic Teachings and Local Customs: A Sociological Study on the Nyadran Tradition in Java - Azzahra, Fatimah; Maulidia Mulyani; Anish Binarsae (SMART: Journal of Sharia, Traditon, and Modernity, 2025)
This article examines the acculturation of Islamic teachings and local customs through a sociological study of the Nyadran tradition in Central Java. The study explores how Islamic values are integrated into local practices while preserving both traditions. It aims to explain how Nyadran functions as a medium for maintaining social harmony, preserving cultural identity, and embedding Islamic values within Javanese customs. This research uses a qualitative method with a literature review approach, analyzing books, journals, and previous studies on religious and cultural acculturation. The theoretical framework draws on sociological perspectives such as structural functionalism, symbolic interactionism, and the sociology of religion. Findings show that Nyadran, originally a form of ancestral veneration, has transformed through Islamic influence into a syncretic tradition involving communal prayers, grave visits, and social gatherings. These activities embody Islamic values like ibadah, muamalah, and birrul walidain. Sociologically, Nyadran serves as a social institution that strengthens religio-cultural identity, fosters social cohesion, and ensures the intergenerational transmission of religious and moral values within a pluralistic society. This study contributes to the discourse on religious acculturation and Islam Nusantara. Keywords: Acculturation; Nyadran; Islamic Teachings; Sociology